Nonstandard forms and measures of employment and unemployment in transition: A comparative study of Estonia, Romania, and Russia - J. David Brown; John S. Earle; Vladimir Gimpelson; Rostislav Kapeliushnikov; Hartmut Lehmann; Álmos Telegdy; Irina Vantu; Ruxandra Visan; Alexandru Voicu (W.E. Upjohn Institute for Employment Research, 2006)
This paper looks behind the standard, publicly available employment and unemployment statistics that studies of transition economy labor markets have typically relied upon. We analyze microdata on detailed labor force survey responses in Russia, Romania, and Estonia to measure nonstandard, boundary forms and alternative definitions of labor force status. Our estimates show that measured employment and unemployment rates are quite sensitive to definition, particularly in the treatment of household production (subsistence agriculture), unpaid family helpers, and discouraged workers, while the categories of part-time work and other forms of marginal attachment are still relatively unimportant. We find that tweaking the official definitions in apparently minor ways can produce alternative employment rates that are sharply higher in Russia but much lower in Romania and slightly lower in Estonia, and alternative unemployment rates that are sharply higher in Romania and moderately higher in Estonia and Russia.
Keywords: J21; 330; Arbeitsmarktstatistik; Statistische Methode; Arbeitslosigkeit; Beschäftigung; Definition; Russland; Rumänien; Estland